Variations of QRS Morphology in Patients with Dilated Cardiomyopathy; Clinical and Prognostic Implications - (:unkn) unknown (My University, 2014)
The QRS represents the simultaneous activation of the right and left ventricles, although most of the QRS waveform is derived from the larger left ventricular musculature. Although normal QRS duration is <100 millisecond (ms), its duration and shape are quite variable from patient to patient in idiopathic dilated cardiomyopathy (IDCM). Prolongation of QRS occurs in 14% to 47% of heart failure (HF) patients. Left bundle branch block (LBBB) is far more common than right bundle branch block (RBBB). Dyssynchronous left ventricular activation due to LBBB and other intraventricular conduction blocks provides the rationale for the use of cardiac resynchronization therapy with biventricular pacing in patients with IDCM. Fragmented QRS (fQRS) is a marker of depolarization abnormality and present in significant number of the patients with IDCM and narrow QRS complexes. It is associated with arrhythmic events and intraventricular dyssynchrony. The purpose of this manuscript is to present an overview on some clinical, echocardiographic and prognostic implications of various QRS morphologies in patients with IDCM.
Keywords: Bundle Branch Block; Fragmented QRS; Idiopathic Dilated Cardiomyopathy